Pengembangan LKPD interaktif untuk pembelajaran berdiferensiasi - Hardiansyah, Hadi; Asmawi, Umi Sumiati; Kamil, Nurdin; Miftakhuddin; Darmansyah, Ady (Universitas Tangerang Raya, 2024)
The concept of conventional worksheets, which are currently widely used in elementary schools, in fact does not have much of a positive impact on science learning outcomes in class. Especially if used in differentiated learning that uses more than one learning method. To overcome this problem, researchers aim to develop Liveworksheet-based Interactive Digital Worksheets that can be used in digitally differentiated learning via PCs or Smartphones. This study uses a research and development methodology with a model popularized by Dick and Carey. The instruments used in this study were interviews, questionnaires and tests. The results of this study are Interactive LKPD on Liveworksheet-based Science learning. Based on the results of the pre-test and post-test analysis, the researchers found significant differences in learning outcomes between these stages with satisfactory final results. So it can be concluded that the Liveworksheet-based Interactive LKPD is able to improve student learning outcomes in science learning in elementary schools